Changes in patient-centered attitude and confidence in communicating with patients: a longitudinal study of resident physicians - Hirono Ishikawa; Daisuke Son; Masato Eto; Kiyoshi Kitamura; Takahiro Kiuchi (BMC Medical Education, 2018)
Abstract Background Patient-centered care has been one of the most frequently discussed principles in medical practice. However, there is a serious concern that the patient-centered attitudes of physicians diminish over the course of their medical education. This longitudinal study examined changes in resident physicians’ patient-centered attitudes and their confidence in communicating with patients, and explored the relationship between the two traits. Methods The study participants were resident physicians at a university hospital in Tokyo. Participants’ patient-centered attitudes (as measured by the Patient–Practitioner Orientation Scale [PPOS]), and their confidence in communicating with patients (as per the Physician Confidence in the Medical Interview scale: [PCMI]) were assessed through self-reported questionnaires completed at the beginning of residency (n = 204) and again at the end of the first year (n = 95). Results PPOS scores declined significantly during the year, both in terms of attitude toward sharing information and decision-making with patients, and attitude of caring for patients’ expectations and emotions. The shift in caring attitude differed significantly by gender. The increase in PCMI score was greater for those with a smaller decrease in PPOS score. Conclusions As seen in previous studies of medical students, resident physicians’ patient-centered attitudes declined during their first year of residency, while there may be a gender-based difference within the shift. The increase in physicians’ confidence in communicating with patients was greater for those who showed a smaller decline in patient-centered attitude. Additional studies are needed to detail the changes in physicians’ attitudes, confidence, and communication skills over the course of their medical training, and to develop systematic assessment and training programs.